2016
DOI: 10.1093/bioinformatics/btw320
|View full text |Cite
|
Sign up to set email alerts
|

Weighted mutual information analysis substantially improves domain-based functional network models

Abstract: Motivation: Functional protein–protein interaction (PPI) networks elucidate molecular pathways underlying complex phenotypes, including those of human diseases. Extrapolation of domain–domain interactions (DDIs) from known PPIs is a major domain-based method for inferring functional PPI networks. However, the protein domain is a functional unit of the protein. Therefore, we should be able to effectively infer functional interactions between proteins based on the co-occurrence of domains.Results: Here, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Then, mutual information scores were computed between domain profiles. We used a weighted mutual information (WMI) scheme, which assigns more weight on rarer domains during mutual information computation (Shim and Lee, 2016;Shim and Lee, 2020). We calculated LLSs for gene pairs using a regression function between WMI and LLS.…”
Section: Inferring Co-functional Links From Protein Domain Profile Asmentioning
confidence: 99%
“…Then, mutual information scores were computed between domain profiles. We used a weighted mutual information (WMI) scheme, which assigns more weight on rarer domains during mutual information computation (Shim and Lee, 2016;Shim and Lee, 2020). We calculated LLSs for gene pairs using a regression function between WMI and LLS.…”
Section: Inferring Co-functional Links From Protein Domain Profile Asmentioning
confidence: 99%
“…We assume the distribution of measurement error is the same for all samples. The density of the observation p xy is different from the density of the true signals p µxµy as shown by equation (2). Our goal is to derive a corrected estimator for mutual information of I(µ x , µ y ) with a reduced bias.…”
Section: Continuous Case: Correcting Estimated Pdf Using Kernel Densimentioning
confidence: 99%
“…Applications of mutual information in computational biology include analyzing the co-evolution relationship between amino acids or nucleotides [1], inferring co-occurrence patterns of protein domains [2], constructing gene regulatory networks [3], studying neural connectivity circuits [4], and so on. An accurate estimation of mutual information is critical to these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require reference PPIs or known DDIs to identify new functional associations between coding genes. Recently, we proposed domain profiling (DP) ( Figure 1 , Inference step C), a domain-based method to infer functional links that requires only domain annotations for each protein coding genes (Shim & Lee 2016 ). In this method, the domain composition of each protein coding gene is represented as a domain profile, which is a vector of presence or absence of each domain of a comprehensive domain database, Interpro (Mitchell et al 2015 ).…”
Section: Inference Of Co-functional Links From Sequencing Datamentioning
confidence: 99%
“…There are various metrics to measure profile similarity. We developed a new metric, a weighted version of MI, and found that this metric outperformed other popular metrics including traditional MI (Shim & Lee 2016 ).…”
Section: Inference Of Co-functional Links From Sequencing Datamentioning
confidence: 99%